2018
DOI: 10.2134/jeq2017.11.0451
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Escherichia coli Concentrations in Sediment before and after High‐Flow Events in a First‐Order Creek

Abstract: Understanding spatial patterns of Escherichia coli in freshwater sediments is necessary to characterize sediments as microbial reservoirs and to evaluate the impact of sediment resuspension on microbial water quality in watersheds. Sediment particle size distributions and streambed E. coli concentrations were measured along a 500‐m‐long reach of a first‐order creek 1 d before and on Days 1, 3, 6, and 10 after each of two artificial high‐flow events, with natural high‐flow events also occurring within the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Rich information on ARG in surface waters can be obtained from the whole genome analysis. Taggar et al (2018) assessed antimicrobial resistance in E. coli recovered from untreated surface‐water sources of dairy farms. Their whole‐genome analysis of multidrug‐resistant isolates identifies multiple ARGs, including blaCMY‐2 and blaCTX‐M‐1, that confer resistance to the critically important extended‐spectrum cephalosporins, as well as a variety of plasmids and class 1 integrons.…”
Section: Antibiotic Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Rich information on ARG in surface waters can be obtained from the whole genome analysis. Taggar et al (2018) assessed antimicrobial resistance in E. coli recovered from untreated surface‐water sources of dairy farms. Their whole‐genome analysis of multidrug‐resistant isolates identifies multiple ARGs, including blaCMY‐2 and blaCTX‐M‐1, that confer resistance to the critically important extended‐spectrum cephalosporins, as well as a variety of plasmids and class 1 integrons.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…Sediment E. coli populations can grow between high-flow events. The rate of such growth was studied by Stocker et al (2018) in highly detailed sampling of streambed sediment across the stream reach before and after artificial and natural highflow events during 1 mo. The authors show that the increase of E. coli in sediment across the reach did occur, but this increase was due to high growth rate in several locations with elevated clay and organic matter contents.…”
Section: Role Of Bottom Sediments and Other Border Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This deviates from conventional thought that resuspension only occurs during high‐flow events (Jamieson et al ). Using artificial floods, Muirhead et al () and Stocker et al () demonstrated roughly two order of magnitude increases in E. coli concentrations that directly resulted from flow rate induced sediment resuspension. This is not surprising, considering that a literature review by Pachepsky and Shelton () noted that E. coli concentrations can be 1 to 2,200 times greater in sediments than in the water column.…”
mentioning
confidence: 99%
“…Nonpoint E. coli sources undergo various fate and transport processes before arriving in streams (Ferguson et al ), thus affecting E. coli and pathogen quantities entering the stream. Regardless of transport mechanism, sediment provides an environmental niche where E. coli can persist for extended periods of time (Garzio‐Hadzick et al ) and potentially grow (Solo‐Gabriele et al ; Stocker et al ). This challenges water managers, as extended persistence and growth can yield E. coli populations that may not be associated with recent contamination events (Anderson et al ), thus diminishing potential relationships between E. coli concentration and human health risk.…”
mentioning
confidence: 99%